A Preliminary Limnological Investigation of Golden- Key Lake, Clemant Town, Uttranchal - Ashok K. Pandit, Showkat Ahmad Lone, Sami Ullah Bhat* and (Current Botany, 2011)
The present study was undertaken to provide some baseline knowledge of the general limnology of Golden Key Lake, Clement town, which stands nearly unstudied artificial lake in Dehradun, India. The investigation was intended to get a coherent picture of the quantitative and qualitative aspects of the lake. This study was undertaken for a short period of time and therefore it should only constitute a starting point for studies imperative for management of these ecosystems of unique nature in the country. Four study sites were selected and analyzed for the main chemical variables and nutrients. An examination of the water chemistry data on comparative level revealed that both ions and nutrients were significantly higher at site I located at a point where sewage water without any treatment enters into the lake.Ã‚Â Computed on an average basis the inorganic elements have been found to follow the sequence: Ca > Na> Mg > K for sites I and II, while for sites III and IV, the sequence was: Ca> Mg>Na>K.